MUSIK HADRAH NURUL IKHWAN DI KABUPATEN PEMALANG: KAJIAN ARANSEMEN DAN ANALISIS MUSIK - nirwanto, bagus (Universitas Negeri Semarang, 2015)
Background of the final project is Hadroh music which is played modernly by Nurul Ikhwan in Pemalang regency, that is with addition of keyboard instrument in the music composition, so that the arrangement is more interested and varied. The problems of this final project are how to arrange Hadroh Nurul Ikhwan music in Pemalang regency and the analysis of Hadroh Nurul Ikhwan music in Pemalang regency. The objectives of the final project are to find out music arrangement of Hadroh Nurul Ikhwan in Pemalang regency and to find out the result of the analysis of Hadroh Nurul Ikhwan music in Pemalang regency. Qualitative with the musicologist approach is used in this final project. Based on the result of the research, Hadroh Nurul Ikhwan music has 4 structures, such as: introduction, song, interlude and coda. The type of arrangement that is used by Hadroh Nurul Ikhwan is mix arrangement. Result of the analysis Hadroh Nurul Ikhwan music. There are 3 kinds of rhythmic pattern which are played with rebana instrument. Those are Golong, Genjring and Tikah. Keyboard is used to fill chord or melody in the introduction, interlude, and coda in the song.